Study of placenta histopathology in low birth weight deliveries: A prospective cross-sectional study at Nobel Medical College Teaching Hospital (Journal of Pathology of Nepal, 2024)
Background: Placenta is the most important organ that represents the status of the mother and fetus. Its examination on gross and microscopy can reveal varied pregnancy-related diseases, decreasing future adverse pregnancy outcomes. This study aims to examine the placenta histopathologically among low birth weight pregnancies.Materials and methods: A prospective case-control study was conducted in the Department of Pathology over one year. The placenta of low birth weight (weight < 2.5 kg) term pregnancies were histopathologically examined. The maternal demographics, co-morbidity, gravida, and hemoglobin levels were recorded. Descriptive statistics, and student t-test or Chi-square test were used for two-group analysis.Results: Thirty-two consecutive patients enrolled in each group. A significant proportion of the patients in the study group were anemic (9.2 vs. 11.5 gm/dl; p=0.03). Pregnancy-induced hypertension rate was significantly higher in the study group (31% vs. 9%; p = 0.042). Gross observations in low birth weight pregnancies were sub-chorionic fibrin deposition (75%), calcification (37%) and infarction (31%). On microscopy, chorionic vessel thrombosis was significantly higher in the study group (56% vs. 6%; p= 0.003). Furthermore, chorioamnionitis (34%) and placental floor infarction (12%) were also observed in a significantly higher number of placentas in the study group.Conclusions: Anemia and pregnancy-induced hypertension are important associated factors for low birth weight pregnancies. Pathological examinations reveal higher fibrin deposition, infarction, calcification, sub-chronic vessel thrombosis, and chorioamnionitis in low birth weight placenta.